Antibiotic Resistance Control Program in Pediatric Hematology and Oncology Patients at Dr. Soetomo Hospital in 2006–2007 - Andarsini, Mia Ratwita; Ugrasena, I Dewa Gede; Permono, Bambang (Institute of Topical Disease Universitas Airlangga, 2010)
Antibiotic resistance has been increasing since the first years of the clinical usage. It caused by inappropriate usage and uncontrol of antibiotic drugs. Therfore an Antibiotic Resistance Control Program (ARCP) is needed to overcome the problem. The purpose of this study is to know microorganism pattern and evaluate antibiotic use. Phase 1 (before ARCP), retrospective study by medical record of pediatric hematology-oncology patients with suspision of infection and admitted at dr Soetomo Hospital from June–August 2006 was carried out. Phase 2 (during ARCP), a prospective observational study was done from November 2006 to January 2007. We were evaluated the isolated microorganism, quantity of antibiotic were determined by Defined Daily Doses (DDD)/100 patients-days, quality of antibiotics usage were assessed with Glyssen classification, and the cost calculation of antibiotic therapy. Twenty seven patients were enrolled in phase 1 and 28 patients in phase 2. Coagulase-negative Staphylococci and Acinetobacter Sp as isolated microorganism was reported. Phase 1, the most sensitive antibiotic was Cefoperazone-Sulbactam and the most resistant was Penicillin G. Phase 2, Meropenem was the most sensitive antibiotic and Cotrimoxazole was the most resistant antibiotic. The use of antibiotics were decreased 6 vs 12 and DDD/100 patients-days were 14.52 vs 45.04. There were improving of Glyssen classification. The cost calculation of antibiotics therapy were decreased. ARCP can improve antibiotic use in pediatric hematology-oncology patients.